PENERAPAN KERJA SAMA EKONOMI DIGITAL INDONESIA-SINGAPURA DI BATAM TAHUN 2017-2018 - Nurichsan Hidayah Putra Harahap; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research aims to explain the implementation of Indonesia-Singapore digital economic cooperation in Batam. The digital economy in Indonesia is developing very fast. Indonesia in increasing the strength of its digital economy is collaborating with Singapore. The governments of Indonesia and Singapore agree on cooperation in digital economy. The author in collecting data uses library research techniques, data is collected from various literature sources such as books, journals, official documents, and websites. The author uses the level of analysis of the nation-state. This research uses the perspective of mercantilism and uses the concept of international economic cooperation.The results of this research indicate that the implementation of digital economic cooperation between Indonesia and Singapore is by establishing Nongsa Digital Park (NDP) in Batam. The NDP is an integrated digital park that provides a place for digital businesses to develop. NDP is one form of infrastructure that supports digital economic activities, especially in digital startup development Keywords : Nongsa Digital Park, Digital Economy, Startup, Information Technology